Protective graphene oxide layers for enhanced stability of copper cathodes in zinc-ion energy storage systems - Nikos Κavousanos; Ricardo Santamaría Ramirez; Athanasia Kostopoulou; Konstantinos Brintakis; Emmanuel Stratakis; Dimitra Vernardou (Discover Electrochemistry)
Abstract The depletion of fossil fuels and growing environmental concerns have intensified the search for alternatives to lithium-ion batteries. Among the promising candidates, zinc-ion energy storage systems, including batteries and hybrid zinc ion capacitors (HZICs), stand out for their safety, cost-effectiveness, high theoretical capacity and scalability. Aqueous zinc-ion energy storage systems are still under investigation, with challenges arising from the aqueous electrolytes, which hinder the development of stable and efficient systems. To address these issues, researchers are actively exploring suitable electrodes and optimizing aqueous electrolytes. In this context, graphene oxide is proposed as a protective layer on the copper electrodes and combined with zinc to create HZIC. Specifically, a depleted layer of graphene oxide was formed by a modified Hummer’s method and electrodeposited on copper substrate. Various deposition times and current densities were explored to tailor the layer thickness and morphology, but also to understand the growth mechanism of this layer, providing valuable insights for its application in sustainable energy storage devices. The optimal conditions were achieved with a three-minute electrodeposition at 0.25 mA/cm2, achieving a capacitance of 32.8 F g−1 and stability for 800 cycles, forming an uneven crystal structure on the electrode surface. Furthermore, the incorporation of ammonium sulfate in the aqueous electrolytes effectively mitigated electrolyte-related issues. Its introduction significantly improved the stability, extending the electrode’s stability to 1500 cycles. However, this enhancement led in a slight initial drop in capacitance, attributed to the increased resistance of Zn+2 interactions with the cathode.